Novel antioxidant protein target therapy to counter the prevalence and severity of SARS-CoV-2 - Kaur, Priyajit; Dey, Akash; Rawat, Kartik; Dey, Sharmistha (Frontiers in Immunology, 2024)
Background:This review analysed the magnitude of COVID-19 pandemic globally and in India and the measures to counter its effect using natural and innate immune booster molecules.The study focuses on two phases, first focuses on the magnitude and the second, the effect of anti-oxidants (natural compounds) on SARS-CoV-2.Methods: Magnitude of prevalence, mortality and co-morbidities were acquired from World health Organization (WHO) report, media, report from Ministry of Health and Family Welfare (MoHFW), News paper, National Centre of Disease Control (NCDC). Research articles from pubmed as well as other sites/ journals and databases were acceseed to gather literature on the effect of anti-oxidants.In elderly and any chronic diseases, the declined level of anti-oxidant molecules enhanced the reactive oxygen species which in turn deprived the immune system.Innate antioxidant proteins like sirtuin and sestrin could play a vital role to enhance immunity.Theherbal products and holistic approaches can also be one of the alternative solutions for everyday life to boost the immune system by improving the redox balance in COVID-19 attack.This review analysed counter of alternative therapy to boost the immune syestem against the magnitude of COVID-19 pandemic.